Analysis of the Influence of Radical Product Innovation on Market Orientation, Market Capabilities, and Electronic Integration in Gadget Technology - Vellina, Yuni (International Journal of Management and Digital Business, 2024)
the researcher intends to be able to determine the influence and significant relationship between each of the variables that have been selected to be analyzed including Radical Product Innovation as the dependent variable, Entrepreneurial Orientations, Marketing Capabilities, Electronic Integration as independent variables, and Proactive Market Orientation as mediating. The author prepared 250 questionnaires which were distributed widely. Proactive Market Orientation is not significant. Meanwhile, the relationship between Marketing Capabilities and Proactive Market Orientation is positive and significant. The relationship between Electronic Integration and Proactive Market Orientation is significant. Apart from that, it is known that Electronic Integration has an influence on Radical Product Innovation. Sedamglam Marketing Capabilities is not significant. towards Radical Product Innovation through Proactive Market Orientation. It is known that the relationship between Proactive Market Orientation and Radical Product Innovation is significant. Also the relationship between Entrepreneurial Orientation and Radical Product Innovation is positive and significant